Numerical modeling of lead-free perovskite solar cell using inorganic charge transport materials. (2020) - Kumar, Anjan; Singh, Sangeeta
Abstract: Ten years after their first mention in report on solar cell implementation, organic-inorganic hybrid perovskites are still the focal point of photovoltaic research. Proper selection of material for different layers has enabled high power conversion efficiency (PCE) values that presently surpass 24%. Unfortunately, the metal halide perovskite solar cells (PSC) contain toxic lead, which is a serious concern for their commercialization process. To tackle lead toxicity issues in perovskite-based solar cells, intensive research by PSC research fraternity is ongoing to develop lead-free metal halide perovskite. In this paper, a novel solar cell configuration which consists of FTO/ Transition Metal Di-Chalcogenides/ Perovskite/ Copper thiocyanate/Au is proposed. In this Transition Metal Di-Chalcogenides (Tungsten Disulfide) is used as an electron transport metal (ETM) due to its high electron mobility and Copper thiocyanate (CuSCN) is used as a hole transport metal (HTM) due to its high transparency and ideal band alignment with perovskite. Impact of variation in thickness of perovskite layer, electron transport layer and hole transport layer on performance parameters were examined. A PCE of 19.84% is achieved at the optimal perovskite layer thickness of 700 nm. When the thickness surpasses 700 nm, PCE drops due to an increase in the recombination of electron-hole pairs. Impact of interfacial defects on the performance parameter was also scrutinized. Simulation results reveal that the interfacial defect of ETM/Perovskite has a larger impact on performance parameters than that of Perovskite/HTM defect when light is irradiated from the ETM side. We also investigated the effect of temperature variation on device performance. The PSC showed optimum performance in the range of 20 °C to 50 °C and the ideal working temperature was viewed as 30 °C.